Language Practices Among Children and Youth in Indonesia - Kushartanti, Bernadette; Djenar, Dwi Noverini (Springer Nature, 2024)
This open access book presents studies of language use in Indonesia, focusing on children and youth. It reports on developments in the use of language for narrative production and within the realm of popular culture and traditional cultural practices in Indonesia. Through studies that include cohesion in narrative production, language in radio advertising, naming practices and formulaic prohibitions in Javanese, and speech presentation in popular fiction, the book provides insights into how sociocultural changes are reflected in language. This book is a useful resource for students and scholars conducting research on language and cultural practices in Indonesia, particularly in relation to children and young people.